THE EFFECTIVENESS OF ACADEMIC SUPERVISION IN IMPROVING THE PERFORMANCE AND COMPETENCE OF LECTURERS IN THE LLDIKTI IV REGION OF WEST JAVA (CASE STUDY AT THE MAHARDIKA INSTITUTE OF CIREBON) - Reni Marlina; Wiwin Awaliyah; Yosi Oktri; Ikka Kartika (International Journal of Teaching and Learning, 2026)
This study aims to evaluate the implementation of academic supervision at Institut Mahardika Cirebon in improving lecturers' performance and competence. Academic supervision is an important element in supporting the implementation of the Tridharma of Higher Education, which includes teaching, research, and community service. This study uses a qualitative descriptive approach with data collection techniques through in-depth interviews, direct observation, and document analysis. The results of the study indicate that the implementation of supervision at Institut Mahardika focuses more on administrative aspects, while supervision of teaching, research, and community service aspects is still running on a limited basis. Some obstacles faced in the implementation of supervision are time constraints, minimal training for supervisors, and lack of supporting facilities. However, academic supervision has had a positive impact in increasing lecturers' awareness of institutional standards and encouraging the development of competence in certain aspects. This study concludes that a more integrated and collaborative supervision approach is needed to address the gap between policy and implementation in the field. Supervision that is not only evaluative but also provides ongoing guidance can be an effective strategy in supporting lecturer professionalism. These findings provide recommendations for other universities in developing a more comprehensive supervision system to improve the quality of higher education.